STRATEGI PEMASARAN MEDIA SOSIAL PADA BRANDING PERUSAHAAN SANDY COLLECTION - Novelia Radista Akbar Gaeni; Natasha Izza Azkia; Endiko Wahyu Normansyah; Laurel Salsabilla Aurora; Ghulyarma Aushafinaz; Latif Ahmad Fauzan; Dian Hutami Rahmawati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research was conducted to determine the startup branding strategy of Sandy Collection. To find out how startup companies start their business to brand their products so that they are more widely known by the public. Sandy Collection on January 12, 2021, started to market its products on the TikTok application and create educational content to get impressions more than 807,000 viewers with more than 23,000 likes. The purpose of this study is to explain the trategy of Sandy Collection company in branding their products using TikTok as social media, so this research focuses on how to brand products on social media. This study used descriptive qualitative method. The informans of this research are the owner of Sandy Collection, Content Creator, Public Relations Sandy Collection, and Social Media Admin. The result of this research is Sandy Collection using 4 social media marketing for company branding: pull strategy, push strategy, endorse, sponsorship.